Relationship between burnout syndrome and age among employees of the Mexican manufacturing industry - Maldonado-Macías, Aide Aracely; Gutiérrez-Hernández, Mónica Gabriela; Barajas-Bustillos, Manuel Alejandro; Rodríguez, Yordán; Realyvásquez-Vargas, Arturo (Frontiers in Psychology, 2025)
IntroductionNowadays, burnout syndrome (BS) has been widely studied due to the increasing and high work demands to which workers are exposed. To date, there is a lack of studies that analyze the relationship between age and its impact on employees in the Mexican manufacturing industry.ObjectiveThis research aims to determine the relationship between BS, its dimensions, and age among operative employees, senior, and middle managers in this industry.MethodsThe 16-item Maslach Burnout Inventory-General Survey (MBI-GS) was used to gather data and measure BS by grade and level. Nine hundred thirty-three employees voluntarily answered the instrument. First, the instrument was validated through psychometric tests to ensure reliability. Kaiser-Meyer-Olkin (KMO) and sphericity tests confirm the feasibility of the factorial analysis. The model’s fit adjustment was tested using structural equation modeling with AMOS. Then, the BS was obtained by grades and levels. Subsequently, the Spearman Rho correlation analysis was carried out between the BS grades by dimension (Emotional exhaustion, Cynicism, and Lack of Professional Efficiency) and age group (up to 40 years and over 40 years). Finally, a hypothesis test for differences between means was conducted to determine whether there were significant differences by BS dimension’s grade regarding age.ResultsThe instrument’s reliability is good, with Cronbach’s alpha value greater than 0.8 for each dimension. The instrument’s structure was confirmed through exploratory factor analysis (EFA). However, the structural equation models do not meet the goodness-of-fit criteria when the sample is divided into two age groups. Furthermore, the entire sample obtained medium grades for each dimension and a medium level of BS. Significant but weak correlations were obtained between age, cynicism, and professional efficiency. The mean test shows significant differences in the dimensions of cynicism (P−value 0.004) and professional efficiency (P-value 0.003). Likewise, the Tukey test with α = 0.05 revealed significant differences in these dimensions between the 51 and 60 age group and the 21-30 and 31-40 age groups.ConclusionThe sample studied has a medium BS level. Accordingly, age exhibits negative and positive correlations with cynicism and professional efficiency, respectively, even when they are weak. Psychometric tests corroborate the instrument’s reliability, not its validity.